Its B

in this kind of Q, start with the easier condition

(2) says

(a^2)(x-y)>0=>(+ve)(x-y)>0

hence x-y=+ve

=>x>y--SUFF

(1) alone is NOT SUFF

--== Message from GMAT Club Team ==--

This is not a quality discussion. It has been retired. If you would like to discuss this question please re-post it in the respective forum. Thank you!

To review the GMAT Club's Forums Posting Guidelines, please follow these links:

Quantitative |

Verbal Please note - we may remove posts that do not follow our posting guidelines. Thank you.

_________________

http://gmatclub.com/forum/math-polygons-87336.html

http://gmatclub.com/forum/competition-for-the-best-gmat-error-log-template-86232.html